Group Theory for the Standard Model of Particle Physics and Beyond - Barnes, Ken J. (Taylor & Francis, 2010)
Based on the author's well-established courses, Group Theory for the Standard Model of Particle Physics and Beyond explores the use of symmetries through descriptions of the techniques of Lie groups and Lie algebras. The text develops the models, theoretical framework, and mathematical tools to understand these symmetries.After linking symmetries w